Activation Policies: New Modes of Governance and the Issue of Responsibility (UNWE Yearbook, 2009)
Most activation policies are based on a simplistic conception of responsibility: behaving responsibly coincides with quickly reintegrating the labour market. Local welfare agents are called to push beneficiaries to actively endorse this goal. But the issue of responsibility is much more complex. Drawing on Sen’s capability approach, this article suggests that responsibilisation of recipients requires both empowerment and granting them more real freedom of choice on the labour market. Against the present trend toward hypertrophying individual responsibility, it calls for a more equilibrated balance between individual and social responsibility. The objective is not to define an impracticable ideal of responsibility, but to provide a yardstick for assessing activation programmes.